2019
DOI: 10.1016/j.drugpo.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Drug safety testing, disposals and dealing in an English field: Exploring the operational and behavioural outcomes of the UK’s first onsite ‘drug checking’ service

Abstract: Background In a year when UK drug-related deaths and festival drug-related deaths reached their highest on record, a pilot festival drug safety testing service was introduced with the aim of reducing drugrelated harm. This paper describes the operational and behavioural outcomes of this pilot and explores the relationship between drug use, supply and policing within festival grounds. Methods Chemists in a temporary laboratory analysed 247 substances submitted by the public to a free, confidential testing servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
166
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(175 citation statements)
references
References 20 publications
7
166
2
Order By: Relevance
“…Drug safety testing disposal rates vary widely depending on composition profiles and adulteration rates identified by forensic analyses, with a review suggesting that disposal rates for testing services ranged from 4–76% and subsequent studies suggesting that the range is even wider. Furthermore, distinctions have been made between intended disposals, actual disposals to a testing service, and verified disposals to an external agency . For example, a Portuguese festival testing service found that almost all service users intended not to take a substance when contents were identified as other than expected (94.3%, n = 86), whereas almost all intended to take it when as expected (98%, n = 370) .…”
Section: Drug Safety Testingmentioning
confidence: 99%
See 3 more Smart Citations
“…Drug safety testing disposal rates vary widely depending on composition profiles and adulteration rates identified by forensic analyses, with a review suggesting that disposal rates for testing services ranged from 4–76% and subsequent studies suggesting that the range is even wider. Furthermore, distinctions have been made between intended disposals, actual disposals to a testing service, and verified disposals to an external agency . For example, a Portuguese festival testing service found that almost all service users intended not to take a substance when contents were identified as other than expected (94.3%, n = 86), whereas almost all intended to take it when as expected (98%, n = 370) .…”
Section: Drug Safety Testingmentioning
confidence: 99%
“…A New Zealand festival testing service survey of 288 respondents found that 62% intended not to take the substance when it was other than expected . The UK's first pilot in 2016 found that over 3/4 (77.8%) of service users whose sample was identified as other than expected intended not to take the substance, with 85.7% of these handing over further substances to the testing service for onwards police destruction …”
Section: Drug Safety Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Chris Ford, clinical director of International Doctors for Healthier Drug Policies and for 30 years a London GP, argues that the existing evidence in the UK and internationally suggests that testing policies don’t encourage drug use but do reduce drug related harms, such as those from contaminants, and that they save lives by reducing overdoses 67. She believes that drug testing is a very useful strategy for harm reduction which, if introduced in the UK, would “categorically save lives.”…”
Section: Going Forwardmentioning
confidence: 99%